DERAJAT VERTEKS GRAF TERHADAP HIMPUNAN VERTEKS - Fauziah Arani; Rolan Pane; Endang Lily (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
This article discusses methods to define the degrees of the graph vertex. These methods include union, intersection, and difference symmetric from vertex set. Based on this definition the relation between the degrees of the graph vertex and vertexset is obtained. An example is given to illustrate the implementation of the methods.